2012
DOI: 10.14712/23362936.2015.34
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound Evaluation of Patients with Moderate and Severe Carpal Tunnel Syndrome

Abstract: The objective of this study is to determine cut-off points for the crosssectional areas of the median nerve proximal and distal to carpal tunnel in moderate and severe Carpal Tunnel Syndrome (CTS) and compare the results of our study with those available in the literature. Forty-three patients with upper limb pain other than CTS and 36 patients with idiopathic CTS enrolled into the study. The diagnosis and categorization of CTS were based on electroph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
1
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 29 publications
(44 reference statements)
1
11
1
2
Order By: Relevance
“…In this study, they accepted cut‐off points of 11.5 and 13.5 mm² for CSA of the proximal and distal portions of the carpal canal, respectively. The sensitivity, specificity, positive and negative predictive values for the proximal inlet were 83%, 90.7%, 65.5% and 55.7%; and for the distal outlet were 36.1%, 93%, 81.2% and 63.4%, respectively . Kwon et al .…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…In this study, they accepted cut‐off points of 11.5 and 13.5 mm² for CSA of the proximal and distal portions of the carpal canal, respectively. The sensitivity, specificity, positive and negative predictive values for the proximal inlet were 83%, 90.7%, 65.5% and 55.7%; and for the distal outlet were 36.1%, 93%, 81.2% and 63.4%, respectively . Kwon et al .…”
Section: Discussionmentioning
confidence: 94%
“…In this study, the difference in CSA of the median nerve in mild, moderate and severe CTS was not statistically significant ( P = 0.2) either in the carpal tunnel inlet or outlet . Moghtaderi et al . suggested that ultrasound is a good diagnostic modality for patients referred to tertiary care centers with categorization as moderate CTS.…”
Section: Discussionmentioning
confidence: 99%
“…In many studies, it has been used to evaluate CTS through measurement of median nerve cross-sectional area (CSA) and calculation of the flattening ratio (FR) (Visser et al 2008). Sonographic measures of CTS are usually obtained at the inlet level, as it is believed that measures at the outlet are technically more difficult and have less inter-rater reliability, though the sensitivity and specificity at both levels are comparable (Moghtaderi et al 2012;Moran et al 2009). …”
Section: Introductionmentioning
confidence: 99%
“…Назначена ЭНМГ верхних конечностей. Амбула-торно в условиях отделения функциональной диагности-сле выхода из запястного канала выявляет значимые из-менения структуры и утолщение ствола нерва [8].…”
Section: результатыunclassified
“…Оптимальной при СЗК является зона запястного канала, объективным параметром неврального пораже-ния -площадь поперечного сечения ствола нерва [7,8]. Остается спорным вопрос о возможности применения УСИ для диагностики степени и характера поражения ствола нерва при СЗК.…”
unclassified